2000
DOI: 10.1093/humrep/15.12.2478
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of ovulation by urinary hormone measurements with the home use ClearPlan® Fertility Monitor: comparison with transvaginal ultrasound scans and serum hormone measurements

Abstract: The timing of sexual intercourse in relation to ovulation strongly influences the chance of conception. Daily serum LH measurements or transvaginal ultrasonography are not practical to determine ovulation in consecutive cycles for an individual. A prospective study was initiated to test the home use performance of the ClearPlan Fertility Monitor (CPFM) in ovulation prediction compared with transvaginal ultrasonography and serum hormone measurements. A total of 53 women aged 18-39 years with a normal uterus and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
158
1
8

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(170 citation statements)
references
References 16 publications
3
158
1
8
Order By: Relevance
“…In no cases did ovulation occur before "peak" fertility. 21 A separate validation study found close correlation between the results of the monitor and laboratory measurements from urine. In 66% of cycles, the LH surge detected by the monitor was on the day of the LH surge detected by laboratory analysis, whereas in 24% it occurred on the day before.…”
Section: Clearplan Easy Fertility Monitormentioning
confidence: 83%
“…In no cases did ovulation occur before "peak" fertility. 21 A separate validation study found close correlation between the results of the monitor and laboratory measurements from urine. In 66% of cycles, the LH surge detected by the monitor was on the day of the LH surge detected by laboratory analysis, whereas in 24% it occurred on the day before.…”
Section: Clearplan Easy Fertility Monitormentioning
confidence: 83%
“…The study of hormonal profiles in urine during the menstrual cycle has proved to be very valuable in understanding menstrual cycle dynamics, as well as variability in ovulation [19,27,28]. Likewise, urinary hormone testing has become an established application for personal monitoring of fertility awareness [9]. Both temperature and hormonal analysis using repeated measurements in menstrual cycles are currently under intensive research as part of the evolving field of digital signal tracking in gynaecological endocrinology [21].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, urinary peak LH day can differ according to the assay used to measure LH in urine, with those detecting beta-core LH (LH-bc) identifying a peak day at least 1 day after assays that do not detect LH-bc [4]. Identification of the day of the urinary LH surge does not appear to be influenced by the assay used, and provides 24-36 h warning of impending ovulation [7][8][9][10], therefore making it an excellent parameter to measure in order to provide prospective information regarding ovulation. Therefore, it is important to have a well-validated method for assignment of the LH surge and to examine retrospective datasets to provide information on population variability of LH surge.…”
Section: Introductionmentioning
confidence: 99%
“…The rise of estradiol in plasma or a metabolite in urine has been suggested as an indicator to the start of the probable fertile phase (15). Other researchers have demonstrated that the CEFM levels of LH and E3G coincide well with the laboratory measurements in defining the potentially fertile period, and found that they follow the increasing concentrations of serum estradiol on the days before ovulation (12,16). They also found the mode warning of ovulation by the CEFM high was 6 days (range, 0-20 days) (12).…”
Section: Intravariability Of the Fertile Windowmentioning
confidence: 93%